2020
DOI: 10.3390/catal10091099
|View full text |Cite
|
Sign up to set email alerts
|

Butane Isomerization as a Diagnostic Tool in the Rational Design of Solid Acid Catalysts

Abstract: The growing demand for isobutane as a vital petrochemical feedstock and chemical intermediate has for many decades surpassed industrial outputs that can be supplied through liquified petroleum gases. Alternative methods to resource the isobutane market have been explored, primarily the isomerization of linear n-butane to the substituted isobutane. To date the isobutane market is valued at over 20 billion US dollars, enticing researchers to seek unique and novel catalytic materials to improve on current commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(75 citation statements)
references
References 188 publications
(341 reference statements)
0
75
0
Order By: Relevance
“…The decalin isomerization reaction is the main competing process of ring opening since it can proceed on the same active sites through both monofunctional (acidic or metal centers) and bifunctional mechanisms. 77 A detailed identification of decalin isomerization products using comprehensive two-dimensional chromatography is available in the literature. 78 The authors have shown that if the number of branching fragments in the carbon skeleton remains constant, then rearrangement occurs by an alkyl shift through the formation of a carbocation on acid sites (type A isomerization).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decalin isomerization reaction is the main competing process of ring opening since it can proceed on the same active sites through both monofunctional (acidic or metal centers) and bifunctional mechanisms. 77 A detailed identification of decalin isomerization products using comprehensive two-dimensional chromatography is available in the literature. 78 The authors have shown that if the number of branching fragments in the carbon skeleton remains constant, then rearrangement occurs by an alkyl shift through the formation of a carbocation on acid sites (type A isomerization).…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that the composition and amount of isomerization products formed on Ir- and Rh-containing catalysts differ significantly. The decalin isomerization reaction is the main competing process of ring opening since it can proceed on the same active sites through both monofunctional (acidic or metal centers) and bifunctional mechanisms . A detailed identification of decalin isomerization products using comprehensive two-dimensional chromatography is available in the literature .…”
Section: Resultsmentioning
confidence: 99%
“…5,55 The large-scale isomerization of n-butane to isobutane is one such relevant example, which also serves as a diagnostic tool for evaluating the performance of an acid catalyst. 174 However, to the best of our knowledge, the molecular Brønsted superacids presented here have not been assessed so far. A first indication of the increased activity of these acids comes from polymerization chemistry.…”
Section: Application In Superelectrophile Catalysismentioning
confidence: 99%
“…However, this should not hide the fact that these superacids have rarely been used in catalysis . This is surprising, considering the vital importance of Brønsted acid catalysis in organic synthesis. Due to their ability to activate inert C­(sp 3 )–H bonds, superacid-based catalysts (mainly in heterogeneous form) also play a central role in the hydrocarbon industry. , The large-scale isomerization of n -butane to isobutane is one such relevant example, which also serves as a diagnostic tool for evaluating the performance of an acid catalyst . However, to the best of our knowledge, the molecular Brønsted superacids presented here have not been assessed so far.…”
Section: Application In Superelectrophile Catalysismentioning
confidence: 99%
“…1 Therefore, the interest in developing more efficient and cost-effective commercial processes for direct isomerization of n-butane and other light alkanes has increased in recent years. [2][3][4][5] Isomerization reaction is generally realized on (strong) acid solids in order to lower the reaction temperature of the skeletal isomerization reaction of light alkanes. 6,7 The best known catalysts for light n-alkanes isomerization at the commercial scale are Pt on chlorinated alumina or Pt/H-mordenite.…”
Section: Introductionmentioning
confidence: 99%